Screening of MicroRNA Related to Irradiation Response and the Regulation Mechanism of miRNA-96-5p in Rectal Cancer Cells - Wu, Fengpeng; Wu, Bingyue; Zhang, Xiaoxiao; Yang, Congrong; Zhou, Chaoxi; Ren, Shuguang; Wang, Jun; Yang, Yafan; Wang, Guiying (Frontiers in Oncology, 2021)
Neoadjuvant chemoradiotherapy has been widely used in the treatment of locally advanced rectal cancer due to the excellent advantages of irradiation in cancer therapy. Unfortunately, not every patient can benefit from this treatment, therefore, it is of great significance to explore biomarkers that can predict irradiation sensitivity. In this study, we screened microRNAs (miRNAs) which were positively correlated with irradiation resistance and found that miRNA-552 and miRNA-183 families were positively correlated with the irradiation resistance of rectal cancer, and found that high expression of miRNA-96-5p enhanced the irradiation resistance of rectal cancer cells through direct regulation of the GPC3 gene and abnormal activation of the canonical Wnt signal transduction pathway. Based on the radioreactivity results of patient-derived xenograft models, this is the first screening report for radio-resistant biomarkers in rectal cancer. Our results suggest that miRNA-96-5p expression is an important factor affecting the radiation response of colorectal cancer cells.